2020
DOI: 10.7150/ijms.48053
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Rational discovery of the therapeutic potential of Melatonin as a SARS-CoV-2 main Protease Inhibitor

Abstract: The SARS-CoV-2 spread quickly across the globe. The World Health Organization (WHO) on March 11 declared COVID-19 a pandemic. The mortality rate, hospital disorders and incalculable economic and social damages, besides the unproven efficacy of the treatments evaluated against COVID-19, raised the need for immediate control of this disease. Therefore, the current study employed in silico tools to rationally identify new possible SARS-CoV-2 main protease (Mpro) inhibitors. That is an enzyme conserved among the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 87 publications
0
63
0
Order By: Relevance
“…184 Furthermore, in silico studies suggest that melatonin inhibits SARS-CoV-2's main protease. 185 It has therefore been suggested that melatonin could be used as prophylaxis or treatment in COVID-19. 186 187 A randomised trial to evaluate the efficacy of melatonin for prophylaxis against SARS-CoV-2 infection in healthcare workers is ongoing.…”
Section: Higher Levels Of Melatoninmentioning
confidence: 99%
“…184 Furthermore, in silico studies suggest that melatonin inhibits SARS-CoV-2's main protease. 185 It has therefore been suggested that melatonin could be used as prophylaxis or treatment in COVID-19. 186 187 A randomised trial to evaluate the efficacy of melatonin for prophylaxis against SARS-CoV-2 infection in healthcare workers is ongoing.…”
Section: Higher Levels Of Melatoninmentioning
confidence: 99%
“…These receptors intervene by activating the renin–angiotensin–aldosterone system (RAAS) and contribute to the appearance of severe lung damage [ 225 ].Furthermore, in vitro studies reported that melatonin inhibits the SARS-CoV-2 major protease (Mpro). The Mpro is an ever present enzyme among the coronavirus species; thus, melatonin identifying itself as an inhibitor of Mpro would become a broad spectrum drug of SARS-CoV-2 [ 226 ]. Moreover, the bats, the main reservoirs of coronavirus, have almost no symptoms associated to the viral infection [ 227 ].…”
Section: Melatonin Supplement For Covid-19mentioning
confidence: 99%
“…The main protease of SARS-CoV-2 is an enzyme conserved among the coronavirus species. By using in silico tools to identify new possible SARS-CoV-2 main protease inhibitors, molecular docking studies described the binding sites and the interaction energies of 74 ligand complexes [ 10 ]. Melatonin revealed better interaction energy with the SARS-CoV-2 main protease than the other ligands.…”
Section: Melatonin In Sars-cov-2 Infectionmentioning
confidence: 99%